Alternative substrate for Hypsizygus Tessellatus Cultivation - Khu, Yong Ming (2017)
The demand of mushroom is increasing annually which open a huge opportunity to developing countries to expand their mushroom industries as the mushroom culturing process converts agriculture waste to profit from crops. Hypsizygus tessellatus is a popular worldwide cultivated edible mushroom which is high in nutrient and medicinal properties. This study is conducted to determine the effect of different parts of the stalk and different strength of potato dextrose agar (PDA) on the mycelium growth of H. tessellatus and to determine the effect of different alternative substrate, namely Dicranopteris linearis (fern leaf), dry leaf of Terminalia catappa and Imperata cylindrica (lalang grass) on the growth of shimeji mushroom, H. tessellatus. The mycelium from the upper and lower part of the mushroom stalk was cultured on half strength and full strength PDA, and the radius of the mycelium growth were measured. Mycelium from the lower part of the stalk have better growth effect. Full strength PDA also shown significantly better growth effect. Full strength PDA also shown significantly better growth effect in mycelium growth. H. tessellatus were cultured on different types of substrate in capsule. Small pieces of D. linearis, I. cylindrical and dried leaf of T. catappa were found suitable to be used as alternative substrate for H. tessellatus cultivation where the mycelium growth in these substrate have no significant difference from the commercially used substrate which is mixture of saw dust and rice bran. The three alternative substrate mentioned above can be found in urban area in large amount which gave opportunity to people couldn’t gain access to the commercial substrate chance to collect their own substrate for mushroom cultivation.